Peran Motivasi dalam Memediasi Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan - Erina Rulianti; Giri Nurpribadi; Roni Amirudin (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
The purpose of this study is to explain the role of motivational mediation on the influence of the work environment on the performance of employees of PT Hung-A Indonesia. This research is quantitative in nature using a questionnaire as a data collection tool. The population in this study were employees of PT Hung-A Indonesai Hi End Factory division with 81 samples obtained from the Slovin formula. The independent variable in this study is the work environment, the dependent variable is employee performance and the work motivation variable is the mediating variable. Data analysis in this study used path analysis. By processing data using Smart PLS 3.0. The results showed that work environment variables had an effect on employee performance. Work environment variables affect motivation. Motivation variables have an effect on employee performance, and motivation is able to mediate the influence of the work environment on employee performance.